Iscriversi ai Corsi di Laurea in Chimica: uno studio sulle motivazioni alla base della scelta - Tarallo, Oreste; Fantozzi, Alexa; Testa, Italo (Chimica nella Scuola, 2025)
Academic drop-out is influenced by a wide range of factors, including social, economic, and psychological aspects. In this preliminary study, we focus on the psychological factors and explore the motivations driving university freshmen to enroll in a chemistry program. To achieve this, we surveyed approximately 1,000 students from various Italian universities, assessing their motivations, attitudes, identity, and self-efficacy in chemistry. A cluster analysis identified four distinct student profiles: Moderately Motivated, Highly Motivated, Differently Motivated, and Failed Admission, each significantly associated with the contextual variables measured. Our findings reveal that fewer than one in five chemistry freshmen are highly motivated, highlighting the need for greater attention to orientation policies at both local and national levels.